In Search of Het Behouden Huys: A Survey of the Remains of the House of Willem Barentsz on Novaya Zemlya - Hacquebord, Louwrens (ARCTIC, 1995)
In August 1992, a Russian-Dutch expedition organized by the Arctic and Antarctic Research Institute in St. Petersburg, Russia and the Arctic Centre of the University of Groningen, The Netherlands surveyed the site of the house of Novaya Zemlya in which the Dutch explorer Willem Barentsz and his crew spent the winter of 1596-97. This survey made it clear that the plundering of the site had been so profound that an excavation would be useless. Comparison of the results of the 1992 survey with the observations made by Elling Carlsen, who discovered the site in 1971, showed that it is improbable that all the remaining objects are still in situ. However, the field study and the supplementary historical research nevertheless cast some new light onto interesting aspects of this notable event in the history of the discovery of the region around the North Pole. The visit to the site made clear that the house was built on a peninsula, and not on the shore of a bay as had been thought up to now. The immediate surroundings turned out to be flat, and not hilly as historical illustrations sugested. It was also evident that these illustrations usually show a mirror image of the house. The house appears to have been constructed in the log cabin manner, with beams which slotted into each other at the corners. The objects found in 1992 made it clear that much handiwork was done during the wintering. The bone material informed us about the diet of the winterers, which consisted of salted beef and fox meat.Key words: Arctic, Russia, Barents Sea, Novaya Zemlya, expeditions, Willem Barentsz, wintering, northeastern passage En août 1992, une expédition russo-néerlandaise montée par l'institut de recherche arctique et antarctique de Saint-Pétersbourg en Russie et par le centre arctique de l'université de Groningue aux Pays-Bas a fait une étude du site de la maison construite en Nouvelle-Zemble, dans laquelle l'explorateur néerlandais Willem Barentsz et son équipage passèrent l'hiver de 1596-97. Cette étude a révélé sans nul doute ...